Pengaruh kandungan vitamin A diet terhadap efek aflatoksin Bi pada status vitamin A tikus Rattus norvegicus - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT Background: Dichlorodiphenyl trichioroetane (DDT), polychlorinated biphenyl (PCB) and polybrominated biphenyl (PBB) are carcinogenic substances and significantly decreased liver vitamin A in the animal studies. Liver vitamin A is influenced by dietary vitamin A and the condition of the liver. Aflatoxin Bi is a carcinogenic substance like DDT, PCB and PBB. Aflatoxin Bi is the environmental exposures problem in several tropical -countries and liver are the main organ targets of the carcinogenicity of aflatoxin Bi. Objective: To provide more extensive description of the effects of dietary vitamin A (deficient, adequate, fourfold adequate) against the effect of aflatoxin Bi (AFBi) on the vitamin A status of rats. Methods: Vitamin A status of animals was demonstrated by concentrations of liver and serum vitamin A. The subjects consisted of fourty eight male Rattus norvegicus rats in good general condition, 1-2 months old with body weight around 62-68.5 grams, were randomly divided into 12 groups of four rats each. Rats in group I to VI which were killed at the start of the experiment and were used as the initial condition of liver and serum vitamin A concentrations for the rats in group VII to XII. Vitamin A-deficient diets were given to rats in group VII and VIII. Vitamin A-adequate diets were given to rats in group IX and X, while vitamin A-fourfold adequate diets were given to rats in group XI and XII. Rats in group VIII, X and XII were orally treated by an aplicator with 15g of AFBï´ in 0.2 ml of propylene glycol everyday for 16 weeks. While rats in group VII, IX and XI were treated without AFBï´. Results: By analysis of variance, the results showed that the effects of interaction of dietary vitamin A and AFBi demonstrated a very significant effect (p